Ordinance no. 61, ch. 16, §§ 1-2, 19, & 28, THE MADISON DAILY LEADER, Oct. 26, 1892, at 4, §§ 1-2, 19, 28 (Madison, South Dakota) - (:unkn) unknown (General Publisher, 1892)
Any person not an officer of the law in the execution of hit duty, who shall in the city of Madison draw a pistol, revolver, knife or other deadly weapon upon another person shall upon conviction thereof, be fined not less than twenty-five nor more than one hundred dollars.Any person who shall in the city of Madison carry concealed about his person any firearm, slungshot, sheath or dirk knife, brass knuckles or any other weapon, which when used is likely to produce death or great bodily harm, shall upon conviction thereof be fined in a sum not exceeding one hundred dollars…Any person who shall in the city of Madison discharge or shoot off any gun, pistol or other firearm, or discharge within the fire limits any firecrackers, rockets or other piece of fireworks, shall upon conviction thereof be fined in any sum not exceeding fifty dollars…
--
Keywords: DISCHARGE; BRANDISHING; CARRY - CONCEALED